Investigation effects of inulin degree of polymerization on compound chocolate quality - Goktas, Hamza; Konar, Nevzat; Sagdic, Osman; Toker, Omer Said (Wiley, 2021)
This is the first study in which the effect of degree of polymerization (DP) (<10 and >= 23) of inulin (6.00, 9.00, and 12.0/100 g) on main quality parameters (color, texture, water activity, sensory properties, and melting behavior) of compound chocolate's (CC) was investigated. According to the determined L* values, using inulin (12/100 g) with high DP resulted in more glossy samples (p < .05). Except increment h value, the melting parameters of CC were not affected. However, the hardness of samples (391.9-587.1 g) was determined in a wide range. The CC samples including inulin with higher DP had higher a(w) values (p < .05). According to the results of sensory analysis, using low DP inulin (<12/100 g) has advantages when compared with higher DP inulin-containing samples. As a result, DP is an important parameter for developing chocolate enriched with inulin as a fiber source, prebiotic, and/or bulking agents. Novelty Impact Statement This is the first study in which the effects of inulin degree of polymerization (DP) and concentrations (6.00, 9.00, and 12.0/100 g) on the main quality parameters of compound chocolate were investigated. The effect of (DP) (<10 and >= 23) of inulin on the main quality parameters of compound chocolate samples as color, texture, water activity, melting behavior, and sensory properties was determined.